ANALISIS KEMAMPUAN HIGHER ORDER THINKING SKILLS (HOTS) MAHASISWA PADA MATERI POKOK KERUSAKAN LINGKUNGAN HIDUP - Irma Indriani (Prodi PGMI STIT Sunan Giri Bima, 2021)
The research aims to describe higher order thinking skills of students semester VII study program PGMI at STIT Sunan Giri Bima on enveiromental damage material using HOTS indicators that include analyze, evaluate, and create. The subject of the research were the students in semester VII PGMI at STIT Sunan Giri Bima of academic year 2018/2019 with the total of 16 students. The instrument of the research were HOTS test. The data analisys amployed descriptive analysis. The results of this study indicate that students' higher order thinking skills on environmental damage material are optimal and meet the three HOTS indicators, namely the aspects of analyzing, evaluating and creating.